Weather Forecast and Warning Portal for Rural Fishermen - Azlee, Johar (2010)
Fishermen put their lives on the brink every time they go out to the sea. This is worse if the weather at the sea is bad. A weather forecast and warning system will help fishermen make better decisions before them to go out to the sea. This will help reduce their costs and help save lives. The main focus of this research is to design a requirement model of the weather forecasting and warning application to rural fishermen by using a portal. At the end of this project, a portal will be designed based on the requirement model of this system. The expectation of this project is that the weather forecast service portal will be fully utilized by the rural fishermen to refer when they require the information about weather anytime anywhere via the Internet.